Can a brief biologically-based psychoeducational intervention reduce stigma and increase help-seeking intentions for depression in young people? A randomised controlled trial - Howard, K.; Griffiths, K.; McKetin, Rebecca; Ma, J. (2018)
© 2018 NISC Pty Ltd There is disagreement in the literature as to whether biological attribution increases or decreases stigma. This study investigated the effect of an online biological intervention on stigma and help-seeking intentions for depression among adolescents. A three-arm, pre-post test, double-blind randomised controlled trial (RCT) was used to compare the effects of a biological and a psychosocial intervention delivered online. Participants comprised secondary school students (N = 327) aged 16–19 years. Outcome measures included anticipated self-stigma for depression (primary), personal stigma, help-seeking intention for depression, and biological and psychosocial attribution. Neither the biological nor the psychosocial educational intervention significantly reduced anticipated self-stigma or personal stigma for depression relative to the control. However, a small increase in help-seeking intention for depression relative to the control was found for the biological educational condition. The study was undertaken over a single session and it is unknown whether the intervention effect on help-seeking intentions was sustained or would translate into help-seeking behaviour. A brief online biological education intervention did not alter stigma, but did promote a small increase in help-seeking intentions for depression among adolescents. This type of intervention may be a practical means for facilitating help-seeking among adolescents with current or future depression treatment needs.